Dampak COVID-19 dan subjective well-being pada lansia - Zainuddin , Ahmad; Rika Monika; Rosyad, Yafi Sabila (Infomasi dan Promosi Kesehatan, 2022)
COVID-19 has an impact on the lives of the elderly such as loss of income, lack of social support, changes in health, violence, neglect, and difficulties in accessing health services, making the elderly vulnerable to changes in well-being during the pandemic. Changes due to the impact are allegedly affecting the happiness and subjective well-being felt by the elderly during the COVID-19 pandemic. This study was to indetify relationship beetwen impact of Covid -19 and Subjective well-being in elderly during Covid -19. This study has used cross – section study design with bivariate analysis data used Kendall's tau. This study involved around 94 respondent using purposive sampling method with criteria inclusion were elderly who are above 60 years old, living with they family, can read, lowest elementary school graduates, and does not suffer from complications. The assessment incuded CAIR Pandemic Impact Questionnaire (C-PIQ), Satisfaction With Life Scale (SWLS) and PANAS. The results of the study on 94 elderly people with an age range of 60 - 80 years, it was found that 68.1% of the elderly felt that Covid-19 had a moderate impact on their lives, there are 36% of the elderly have life satisfaction in the quite dissatisfied category, and 33% of the elderly felt negative feelings during the pandemic. There is a relationship between the impact of COVID-19 and Life Satisfaction with pvalue (0.003) < (0.05). There is a relationship between the impact of COVID-19 and PANAS (0.006) < (0.05). The impact of COVID-19 has a significant relationship on Subjective Well-Being in the elderly.